Implementation of Sustainable Supply Chain Management in Organic Rhizome Supply Partnership - Novra, Ardi; Asyar, Rayandra; Adriani, Adriani; Marwan, Husda; Mursalim, Mursalim; Achmad, Eva (Technium Social Sciences Journal, 2022)
The purpose of this paper is to identify and evaluate the implementation of Sustainable SCM in organic rhizome supply partnerships which includes 7 aspects. The program developed multi-stakeholder partnership governance within a supply chain management (SCM) framework for organic rhizome agroindustry. Stakeholders involved in partnerships are grouped into 3 according to the components in SCM, namely 1) downstream SC who provide input needs for organic rhizome cultivation (producers of compost, cocopit and other planting media), 2) internal SC who carry out the cultivation process starting from the Organic Rhizome Learning Center (until the age of 4 months) and households rhizome cultivation, and 3) upstream SC, namely households (post-harvest and processing). The evaluation results show that of the seven aspects of SSCM, only the logistics aspect is optimized and the transportation is sustainable, while the other 6 aspects are already running. The use of organic waste available for seedling and planting media meets the aspect of a sustainable source of raw materials, is able to reduce the risk of concentration in nature so as to reduce risks to occupational health and safety. Development of research and learning centers in each target village as a means of sharing in sustainable competency development. On the other hand, with tiered partnerships involving customers, suppliers, communities and community groups with government and university facilitation, the model built has a positive impact on local communities. Based on the three aspects of sustainable development, the development of a multi-stakeholder partnership model in this organic rhizome agroindustry can be a best practice for other commodities.